Creative minds, healthy minds: strategi menjaga kesehatan mental mahasiswa melalui kegiatan kreatif di kampus - Nadiya, Roudlotul; Khojidah, Khojidah (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: University students face various pressures such as academic stress, social transitions, and identity development that can impact their mental health. Creative activities are considered as an alternative approach to maintaining students’ emotional balance. Purpose: To determine the role of creative activities in maintaining students’ mental well-being. Method: A qualitative research with a phenomenological approach. In-depth interviews were conducted with five students from Universitas Islam Negeri Sunan Ampel Surabaya to explore their experiences in engaging with creative activities. Results: The results showed that participating in activities such as writing poetry, painting, music, and performing arts helped students express emotions, boost self-confidence, reduce academic stress, and foster a sense of community. Main barriers identified were time constraints, social stigma, lack of information, and limited institutional support. Conclusion: Creative activities significantly contribute to students’ mental well-being. Therefore, institutional support is essential to ensure equitable access and sustainable implementation of creative programs in higher education. Keywords: Academic stress; Creative activities; Mental health; Self-expression; University Students. Pendahuluan: Mahasiswa menghadapi berbagai tekanan seperti stres akademik, transisi sosial, dan pencarian identitas diri yang dapat berdampak pada kesehatan mental. Kegiatan kreatif dipandang sebagai salah satu alternatif dalam menjaga keseimbangan emosional mahasiswa. Tujuan: Untuk mengetahui peran kegiatan kreatif dalam menjaga kesehatan mental mahasiswa. Metode: Kualitatif dengan metode fenomenologi. Wawancara mendalam dilakukan terhadap lima mahasiswa Universitas Islam Negeri Sunan Ampel Surabaya untuk menggali pengalaman mereka dalam kegiatan kreatif. Hasil: Keterlibatan dalam praktik kreatif seperti menulis puisi, melukis, bermusik, dan seni pertunjukan membantu dalam mengekspresikan emosi, meningkatkan kepercayaan diri, mengurangi stres akademik, serta membantu rasa kebersamaa. Namun demikian, keterbatasan waktu, stigma, kurangnya informasi, dan dukungan institusional yang minim menjadi hambatan utama. Simpulan: Kegiatan kreatif bukan hanya hiburan semata, tetapi menjadi strategi penting dalam meningkatkan ketahanan psikologis dan kesejahteraan emosional mahasiswa. Kebijakan kampus yang inklusif dan mendukung sangat diperlukan untuk menjamin akses yang setara dan pelaksanaan program kreatif yang berkelanjutan. Kata Kunci: Ekspresi Diri; Kegiatan Kreatif; Kesehatan Mental; Mahasiswa; Stres Akademis.